2014
DOI: 10.1093/jac/dku161
|View full text |Cite
|
Sign up to set email alerts
|

Detection of mutations associated with isoniazid resistance in multidrug-resistant Mycobacterium tuberculosis clinical isolates

Abstract: This study accentuates the usefulness of katG and inhA promoter mutations as predictive markers of isoniazid resistance. Testing only for katG 315 and inhA -15 mutations would detect isoniazid resistance in 84% of the MDR M. tuberculosis sample. This percentage would increase to 96% if the sequence analysis was extended to the entire katG gene. Analysis of the remaining genetic loci did not contribute greatly to the identification of isoniazid resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 27 publications
5
46
0
Order By: Relevance
“…All isolates of the LAM lineage had alteration at nucleotide 513 in the rrs gene. Several studies have reported rrs mutations in this lineage [12,32]. Based on MIRU-VNTR genotyping, the most prevalent genotype was Beijing.…”
Section: Discussionmentioning
confidence: 99%
“…All isolates of the LAM lineage had alteration at nucleotide 513 in the rrs gene. Several studies have reported rrs mutations in this lineage [12,32]. Based on MIRU-VNTR genotyping, the most prevalent genotype was Beijing.…”
Section: Discussionmentioning
confidence: 99%
“…The mutation-carrying genes, such as those encoding the enzymes KatG (11,12) and EthA (13,14), are associated with individual resistance to INH and ETH, respectively. Mutations at the inhA promoter region or inhA gene result in the overexpression or modification of the InhA target, causing cross-resistance to INH and ETH (8,15).…”
Section: Ethionamide (Eth) Is An Antibiotic Used For the Treatment Ofmentioning
confidence: 99%
“…The transmission of strains resistant to both rifampin (RIF) and isoniazid (INH), i.e., multidrug-resistant (MDR) strains, remains a public health problem. These strains may harbor mutations in rpoB (2,3), katG, and inhA, among other genomic regions (4,5). The aim of this study was to evaluate the diagnostic accuracy of the GenoFlow DR-MTB array test (DiagCor Bioscience, Hong Kong) for the detection of M. tuberculosis molecular resistance to RIF and INH.…”
mentioning
confidence: 99%